Universal high voltage recorder for testing laboratories - Khamlichi, Abderrahim (2021)
Traditionally, high-voltage (HV) laboratories have required different measuring instruments to measure alternating voltages 50/60 Hz (AC), using peak voltmeters, lightning impulses, through peak voltage meters and oscilloscopes and the apparent load, by means of partial discharge (PD) measuring instruments. All of them with very different technical requirements included in standards applicable to hardware and software (standards of the IEC 61083 [1] series and IEC 60270 [2] standard). However, the technological evolution of measuring instruments has allowed these measurements could be carried out through high-performance digital A/D recorders. This article describes the new measuring system developed by the LCOE “Universal High Voltage Recorder”, known as “RUAT”, capable of being used for the five typical measurements of high voltage in a laboratory: AC, DC, lightning impulse (1.2/50 µs), switching impulse (250/2500 µs) and PD.